Sustainability criteria for the selection of water supply pipeline. Issue 1 (1st January 2018) - Maiolo, Mario; Capano, Gilda; Carini, Manuela; Pantusa, Daniela
Abstract: The evolution of the materials used for drinking water pipelines has often introduced substantial innovations in the market, both in terms of improved static and hydraulic performance and cost. Over time, technical and cost-effective assessments to pipelines selection, related to the materials used, have been accompanied by environmental assessments in relation to the environmental impact of construction and management of drinking water system. The recent legislative and technical regulations have made the environmental cost assessment more complex, which is related to the life cycle of materials and infrastructures. This paper proposes an index, In Situ Sustainability Index (ISSI), which can be used for the pipelines materials choice for drinking water systems and which takes into account both technical and environmental aspects. This index considers the interaction between piping and laying soil, through the In Situ Elasticity Coefficient and the impacts of materials used for water system piping through Life Cycle Assessment. The ISSI index is a practical tool because it makes a simultaneous consideration of two essential aspects in the design (technical and environmental evaluations) through a rapid-use analytical structure.